2000
DOI: 10.1111/j.174-1617.2000.tb00580.x
|View full text |Cite
|
Sign up to set email alerts
|

CHILD PROTECTION EVALUATIONS The Forensic Stepchild

Abstract: In child protection cases, the mental health evaluator is required to have a broad range of expertise in family violence and child and adult psychological issues. This article reviews epidemiological as well as other quantitative data to provide an empirical foundation by which to understand the problem of family violence, the characteristics of abusers and victims, and the consequences to the child who is a witness to or victim of family violence. Forensic evaluation guidelines and recommendations for structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 65 publications
1
27
0
Order By: Relevance
“…Nonetheless, some parents' IQs fell in the mentally retarded range (IQ score of 70 or below for 6 mothers), in the borderline range (71-80 for 13 mothers and 3 fathers), or in the low average range (81-90 for 12 mothers and 3 fathers). These findings are in accord with other published descriptions of parents undergoing PCA (e.g., Azar et al, 1998;Kuehnle et al, 2000), although our results are the first formal assessment and reporting of intellectual and demographic characteristics of this population. In light of the fact that a considerable number of these parents functioned below the average range, we evaluated the relationship between intelligence scores and validity-scale elevations to rule out the possibility that elevations were not simply a function of the inability to understand the test items.…”
Section: The Investigationsupporting
confidence: 94%
“…Nonetheless, some parents' IQs fell in the mentally retarded range (IQ score of 70 or below for 6 mothers), in the borderline range (71-80 for 13 mothers and 3 fathers), or in the low average range (81-90 for 12 mothers and 3 fathers). These findings are in accord with other published descriptions of parents undergoing PCA (e.g., Azar et al, 1998;Kuehnle et al, 2000), although our results are the first formal assessment and reporting of intellectual and demographic characteristics of this population. In light of the fact that a considerable number of these parents functioned below the average range, we evaluated the relationship between intelligence scores and validity-scale elevations to rule out the possibility that elevations were not simply a function of the inability to understand the test items.…”
Section: The Investigationsupporting
confidence: 94%
“…The guidelines informing the decisions about fitness to be parents were taken from risk factors defined by Kuehnle, Coulter & Firestone [18]. In determining fitness to be parents, many factors were considered, apart from levels of intelligence or cognitive impairment.…”
Section: Participantsmentioning
confidence: 99%
“…In order to conclude that child abuse has occurred, several sources should concur regarding the type, timing, and circumstances of the abuse. and girls are more often abused by family members whereas boys are more often abused by individuals outside the family (Kuehnle et al, 2000). 8.…”
Section: Multiples Sources Of Informationmentioning
confidence: 99%
“…Nevertheless, researchers have estimated that only 30% of abused children become abusive parents (Kaufman & Zigler, 1987). We do not know how the 70% of non-abusive parents with personal histories of child abuse overcome their own abusive histories, but research has shown that the development of a realistic understanding of one's own maltreatment history is associated with strong parenting skills in mothers (Kuehnle et al, 2000). 13.…”
Section: Multiples Sources Of Informationmentioning
confidence: 99%
See 1 more Smart Citation